Materials for Sustainable Construction Engineering - Putra Jaya, Ramadhansyah (Trans Tech Publications, Switzerland, 2022)
Selected peer-reviewed full text papers from the World Sustainable Construction Conference (WSCC) Series 2021, October 29-30, 2021, Gambang, Malaysia